KNOWLEDGE MANAGEMENT IN SECONDARY SCHOOLS: A CONCEPTUAL MODEL WITH GROUNDED THEORY APPROACH - MehryDaraei, AbdolrahimNavehebrahim, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Aim/purpose:The present paper examines the viewpoints in the literature regarding knowledge management and delimits the need to address the variables which influence and explain the knowledge management procees in Iranian secondary schools and the authors aim to design the theoretical model of KM wity Grounded theory. Methodology: The Grounded Theory methodology was chosen due to its ability to extract theory from data. After having viewed the theoretical literature related to the subject of the study, whether it was provided in references or in scientific journals and theses. This study is an exploratory, analytical study and follows the approach of collecting and analysing data to draw conclusionsThe qualitative research focused on 14 in-depth semi-structured interviews with professionals from the Iranina education sector. Findings:The results of data analysis(Three stage coding) showed 280 open code, 116 concepts and 16 categories have been classified and organized according to their connections with each other and the perspective they envisage.Finally we will present all the main variables with their sub-elements, adequate correlations in literature and citations from the in-depth interviews undertaken.Designed model is consist of componenets,causalfactors,axialfactors,strategies,axial phenomenon and consequences. Implications & Recommendations: This study offers a deeper understanding of knowledge management process for educational administrators and teachers. This study is also of value in managerial perspective as it helps they to improve their practices by use of individual and organizational consecouences of knowledegmanagement . Most interviewees might accept that KM can help improve their practice but it needs the support of various dimensions such as Knowledge-based culture,humanfactor,technical support and managerial factors.